Corrigendum: Transcriptome-based phylogenomic analysis reveals evidence of ancient hybridization events in the Mepraia genus (Hemiptera: Reduviidae: Triatominae) (Frontiers in Ecology and Evolution, (2023), 11, (1215319), 10.3389/fevo.2023.1215319) - Belintani, Tiago [UNESP] (2023)
In the published article, an author name was incorrectly written as “Daniel Frías Lasserre”. The correct spelling is “Daniel Frias-Lasserre”. Another name was incorrectly written as “João Aristeu Da Rosa”. The correct spelling is “João Aristeu da Rosa”. In the published article, there was an error in affiliations 2 and 3. The affiliations were listed incorrectly as: 2 Department of Plant and Environmental Protection Services, University of Hawaii at Manoa, Honolulu, HI 96822, USA 3 São Paulo State University (Unesp), School of Pharmaceutical Sciences, Araraquara, SP, Brazil. The corrected affiliations are below: 2 School of Pharmaceutical Sciences, São Paulo State University (Unesp), Araraquara, SP, Brazil 3 Department of Plant and Environmental Protection Services, University of Hawaii at Manoa, Honolulu, HI, United States The authors apologize for this error and state that this does not change the scientific conclusions of the article in any way. The original article has been updated.